SWOT Analysis Quick Response Indonesian Standard (QRIS) As a Digital Payment System (Cashless) Towards Advanced Indonesia - Martin Teddy Sihite; Kristoko Dwi Hartomo (Budapest International Research and Critics University, 2022)
Bank Indonesia together with the Financial Services Authority officially launched the Quick Response Indonesian Standard (QRIS) for the first time at the Bank Indonesia head office on August 17, 2019 and has been effective nationally since January 1, 2020. The SWOT analysis in this study aims to see the identification of problems found from the use of this QRIS digital payment system. IFAS and EFAS calculations are carried out in obtaining the number of points for each SWOT element by determining the coordinates of the SWOT Analysis Graph using a Cartesian Diagram. Based on the results of the research, the conclusion states that the results of Strength (QRIS Strength) are 1289 Points (37.2%), Weakness (QRIS Weaknesses) are 277 Points (8%), Opportunity (QRIS Opportunity) is 1284 points (37.1%) and Threat (QRIS Threat) as much as 610 points (17.6%). The final result of the study proves that the QRIS digital payment system is very feasible to use because the results of the SWOT analysis graph depicting the coordinates (X and Y) are located in the (Strength and Opportunity) section with the acquisition of the coordinates (X, Y) of (1012, 674). This means that Strength QRIS far outperforms 1012 points compared to Weakness QRIS and Opportunity QRIS outperforms 674 points compared to Threat QRIS, thereby proving that the community agrees and supports the use of the Quick Response Indonesian Standard (QRIS).